Marketplace nos agronegócios: fatores que influenciam o uso e adesão do e-commerce entre produtores rurais gaúchos - Portal, Mariana Juliani da Silva (2024)
Electronic commerce (e-commerce) offers new market opportunities for agribusinesses. With the advance of information and communication technologies, e-commerce is a process that is gaining momentum all over the world, due to the benefits it brings to consumers and organizations. In the agribusiness sector, it is still a recent phenomenon and there are many challenges to overcome, including getting rural producers on board with the new marketing formats and new technologies. Among the most popular e-commerce models is the marketplace, which usually includes robust marketing platforms, making it possible to buy and sell products or services on the same technology. However, there are still research gaps on the subject of marketplaces in agribusiness, specifically in Brazil and emerging countries. The aim of this study was to analyze the use and uptake of marketplaces in agribusinesses in Rio Grande do Sul - Brazil. The research is classified as quantitative and exploratory, using two questionnaires as a data collection instrument, which totaled 140 respondents. The instruments were made available via the Google Forms platform and applied in person at Expodireto 2024. Questionnaire 1 was aimed at rural producers from Rio Grande do Sul who make online purchases, in order to test a proposed theoretical model on marketplace adherence in agribusiness. The theoretical model to be explored was based on the TAM, UTAUT2 and Integrated Theoretical Model of Trust models used to investigate technology adoption. Questionnaire 2 was directed at rural producers from Rio Grande do Sul who do not buy online, in order to understand the reasons for their non-adherence. Structural Equation Modeling (PLS-SEM) was used to analyze the results related to the proposed theoretical model. For the rest of the data, we opted for simple descriptive analyses of mean, frequency and percentage. The results show that the majority of rural producers in Rio Grande do not buy online. Younger respondents, in particular, tend to be more active online shoppers. With regard to education, it was found that the higher the level of education, the greater the propensity to shop online. The size of the production area does not significantly affect the adoption of new technologies. For rural producers who buy online, using e-commerce is easy, safe, pleasant and convenient. The main perceived risks are related to after-sales service and the veracity of information, but rural producers in Rio Grande do Sul intend to continue buying online more often. With regard to producers who don't buy online, there was a preference for face-to-face service, fear of scams and the need for technical assistance. These are the main reasons why rural producers in Rio Grande do not buy online. Finally, the study confirmed the hypotheses of the theoretical model, indicating that, despite the challenges, the marketplace has the potential to transform agribusiness. The research suggests that, in order to increase take-up, it is essential to address concerns about security and support, as well as promoting digital education among producers.